Analysis of risk factors that influence events hypertension pre-elderly - Hadi, Nursini Juiban; Saimi, Saimi (Institute of Computer Science (IOCS), 2024)
Hypertension is one of disease chronic affects global health, especially in populations pre-elderly. Identification factor influencing risks incident hypertension at stage pre-elderly can give valuable insight _ For effort appropriate prevention and intervention _ time, potential reduce burden disease, as well increase quality life and hope life for affected individual _ impact. Research purposes This is for identify and analyze factors contributing risks _ to incident hypertension in the population pre-elderly. Study This use design cross-sectional study. Data collection methods used in study This is survey method. Data analysis using analysis bivariate and multivariate. Research result show that factor age, breed, habits smoking, alcohol consumption, soft drink consumption are variables that don't relate with factor risk incident hypertension in the elderly. Whereas factor history family, stressors, obesity, activity physical, consuming food high fat, habit consume food salty, habitual drinking coffee > 3 times a day, consuming junk food is variable that becomes factor risk incident hypertension in the elderly.